Learning Route 2014 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Learning Route on Natural Resources Management and Climate Change Adaptation best practices covered several districts in Kenya. The event was organized by Procasur with the support of the International Fund for Agricultural Development (IFAD. Photos: P. Kimeli (CCAFS)